Experimental investigation on the repair of rammed earth by means of injection of mud grouts - Silva, Rui André Martins (2014)
This paper assesses the adhesion capacity of unmodified mud grouts used to repair structural cracks on medium and large scale rammed earth specimens. Beam and wallet-specimens were manufactured using a soil from Alentejo (Portugal), whose particle size distribution had to be first corrected due to its high clay content. An “artificial” (composed by kaolin and limestone powder) and a “natural” (composed by sieved soil and limestone powder) mud grout were used to repair the specimens, which were previously tested under three-point bending and diagonal-compression and then retested. The grout injection shown to provide satisfactory results regarding the adhesion capacity, but only if it is performed with the “natural” mud grout.